Status Of Trace Elements During Oestrus Cycle In Regular And Repeat Breeding Red Kandhari Cows - Shahapure , S. N.; Kekan, P. M. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to evaluate the status of trace elements in regular and repeat breeding Red Kandhari cows. The average serum copper, zinc, manganese, iron and cobalt values in repeat breeder cows were 0.43 ± 0.03, 1.21 ± 0.12, 0.30 ± 0.00, 0.89 ± 0.01 and 0.039 ± 0.001 ppm, respectively, which were significantly lower than the values of 0.62 ± 0.04, 2.02 ± 0.02, 0.55 ± 0.03, 1.32 ± 0.02 and 0.048 ± 0.004 ppm, respectively in regular breeder cows.
Keywords: Trace elements; Repeat breeding; Regular breeding; oestrus cycle; Kandhari cows